Analisa Waktu Tunggu Dalam Pelayanan Resep pada Pasien Rawat Jalan di Instalasi Farmasi RSUD dr. Hadrianus Sinaga Pangururan Tahun 2023 - Dewi Ginting, Fitri; Manurung, Kesaktian; E Sitorus, Mido; Nababan, Donal; Lina Tarigan, Frida (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Quality of health services is one approach or effort that is fundamental in providing health services to patients. As a professional person in the field of health services, both individually and in groups, you must always try to provide good quality health services to all patients, Without exception. One of the most essential parts of a hospital is the pharmacy installation. Pharmacy installations are an inseparable part of a complete hospital health service system. The pharmacy installation is responsible for procuring and presenting drug information to all parties in the hospital and developing extensive and well-coordinated pharmaceutical services to meet and provide good service to patients. Servicing old prescriptions to outpatients in the pharmacy installation can cause patient dissatisfaction, impacting the quality of service and hospital. This makes researchers interested in analyzing the waiting time in prescription services for outpatients in the pharmacy installation at RSUD dr. Hadrianus Sinaga Pangururan in 2023. Research Focus on Waiting Times for Prescription Services for Outpatients at the Pharmacy Installation at RSUD dr. Hadrianus Sinaga Pangururan in 2023. The research subfocus is: What is the flow of patient prescription services, what causes the lengthening of waiting times for patient prescription services, and what is the impact of extending waiting times for outpatient prescription services at the pharmacy installation at RSUD Dr. Hadrianus Sinaga Pangururan? Type of Research: This research is survey research using a qualitative approach and an in-depth interview method. Research Location: This research was carried out at RSUD dr. Hadrianus Sinaga Pangururan. Based on the research results on analyzing waiting times for outpatient services at the pharmacy installation at RSU dr. Hadrianus Sinaga In 2023, the results can be taken: The lengthening of waiting times that occurs in Outpatient Pharmacy Installations due to the availability of medicines that often happen in vacancies. The extended waiting time occurs in the Outpatient Pharmacy Installation because writing labels takes a long time. The extended waiting time at the Outpatient Pharmacy Installation is due to taking one month's prescription, which must go through the verification stage. The impact of extending the waiting time in the Outpatient Pharmacy Installation is that patients' dissatisfaction is indicated by protesting and getting angry. The effect of lengthening waiting times in Outpatient Pharmacy Installations due to the unavailability of medicines causes patient management to be hampered.